Perioperative Factors and Their Effect on the Fibrinolytic System in Arthroplasty Patients. (April 2016) - Burleson, Andrew; Guler, Nil; Banos, Andrew; Syed, Daneyal; Wanderling, Christopher; Hoppensteadt, Debra; Rees, Harold; Fareed, Jawed; Hopkinson, William
Background: Total joint arthroplasty (TJA) patients are mostly of advanced age and with comorbidities such as increased body mass index (BMI) and impaired glucose tolerance. These factors and type of surgery may affect the fibrinolytic system. Aim: To investigate the effect of age, sex, BMI, type of surgery, and tranexamic acid (TXA) treatment on the fibrinolytic system in TJA patients. Methods: Ninety-nine patients undergoing TJA (32 total hip arthroplasty [THA] and 67 total knee arthroplasty [TKA]) were included in this study. Blood samples were drawn at preoperative clinic appointments and on postoperative day 1. Antigenic levels ofd -dimer, plasminogen activator inhibitor 1 (PAI-1), and tissue plasminogen activator (tPA) were measured using a commercially available enzyme-linked immunosorbent assay kit. Antiplasmin activity was measured using functional method. Age, gender, hemoglobin (Hb) levels, and BMI were collected from the records. Results: Preoperatived -dimer and tPA levels were positively correlated with age, whereas preoperative antiplasmin was negatively correlated with age. Body mass index was only associated with preoperative tPA levels. There was no significant difference in postoperative levels ofd -dimer, PAI-1, tPA, or antiplasmin between patients treated with TXA or without TXA. Percentage change ind -dimer and tPA showed significantly lower values in patients treated with TXA compared to the nontreated group. Type of surgery did not affect the fibrinolytic markers. Conclusion: These results confirm that advanced age and elevated BMI positively contribute to fibrinolytic dysregulation in TJA patients, whereas TXA seems to decrease the fibrinolytic activity.